ERROR CORRECTION MODEL APPROACH AS A DETERMINANT OF STOCK PRICES - Fatmasari, Dewi; Harjadi, Dikdik; Hamzah, Amir (TRIKONOMIKA, 2022)
The short-term and long-term effects of ROI, EPS, PER Inflation, SBI, Exchange Rate, and GDP on the stock price are the focus of this study. The study's data came from company financial statements, including the Indonesian Stock Exchange Index LQ45. The stationarity test, the classical assumptions test, the cointegration test, and the error correction model test was utilized in this study's statistical analysis. KURS and SBI had a positive effect on stock prices in the short term, but there is no effect in the long term, and inflation and GDP do not affect the stock price both in the short term and in the long term, according to this study. As a result, investors and businesses can use this study's contribution as a point of reference when considering factors that have a short-term and long-term impact on stock prices.